Antioxidant and α‐glucosidase inhibitory activities and gas chromatography–mass spectrometry pro le of salak (salacca zalacca) fruit peel extracts - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Mat So'ad, Siti Zaiton; Murugesu, Suganya; Khatib, Alfi; Rahman, Md. Mokhlesur (Wolters Kluwer ‐ Medknow, 2018)
Background: This study was aimed to investigate antioxidant and α‑glucosidase inhibitory activity, with a proximate analysis of total phenolic and total flavonoid content with gas chromatography–mass spectrometry (GC‑MS) profiling of salak (Salacca zalacca) fruit peel extracts. Materials and Methods: The peels extracts were prepared by maceration process at room temperature with different ratio of ethanol/water. Results: Phytochemical screening showed the presence of phenolic and flavonoid contents in all the extracts. About 100% ethanol extract shows the highest phenolic content (116.70 ± 0.764 μg/mL) while 60% ethanol extract has the lowest content 18.65 ± 1.155 μg/ml using gallic acid as a reference. 100% ethanol extract was observed to exhibit highest radical scavenging, ferric reducing antioxidant power (FRAP), and α‑glucosidaseinhibitory activities (IC50: 49.45 ± 3.87 μg/mL, 144.81 ± 3.72 μg AAE/g,IC50: 11.62 ± 0.67b μg/mL), respectively. Water extracts had the lowestFRAP, radical scavenging activity as well as α‑glucosidase activity. The phytochemical investigation on GC‑MS showed the presence of active compounds in salak fruit peel extracts. Conclusion: Salak fruit peels showed the highest antioxidant as well as α‑glucosidase inhibitory activities. Phytochemical analysis on GC‑MS confirms the presence of gallic acid, linoelaidic acid, palmitic acid, α‑tocopherol, and steric acid whichmay contribute to α‑glucosidase inhibitory activity.